LO056: Perceptions and provision of analgesia for acutely painful conditions in children: a multi-centre prospective survey of caregivers. (2nd June 2016) - Wonnacott, D.; Poonai, C.; Wright, B.; Ali, S.; Bhat, C.; Todorovich, S.; Mishra, A.; Canton, K.; Rajagopal, M.; Thompson, G.C.; Stang, A.S.; Poonai, N.
Abstract : Introduction: The suboptimal management of children's pain in the emergency department (ED) is well described. Although surveys of physicians show improvements in providing analgesia, institutional audits suggest otherwise. One reason may be patient refusal. Our objectives were to determine the proportion of caregivers that offered analgesia prior to arrival to the ED, accept analgesia in the ED, and identify reasons for withholding analgesia. Our results will inform knowledge translation initiatives to improve analgesic provision to children.Methods: A novel survey was designed to test the hypothesis that a large proportion of caregivers withhold and refuse analgesia. Over a 16-week period across two Canadian paediatric EDs, we surveyed caregivers of children aged 4-17 years with an acutely painful condition (headache, otalgia, sore throat, abdominal pain, or musculoskeletal injury). The primary outcome was the proportion of caregivers who offered analgesia up to 24 hours prior to ED arrival and accepted analgesia in the ED.Results: The response rate was 568/707 (80.3%). The majority of caregivers were female (426/568, 75%), aged 36 years or older (434/568, 76.4%), and had a post-secondary education (448/561, 79.9%). Their children included 320 males and 248 females with a mean age of 10.6 years. Most (514/564, 91.1%) reported being "able to tell when their child was in pain". On average, children rated their maximal pain at 7.4/10. A total of 382/561 (68.1%) caregivers did not offer any form of analgesia prior to arrival. Common reasons included lack of time (124/561, 22.1%), fear of masking signs and symptoms (74/561, 13.2%) or the seriousness of their child's condition (72/561, 12.8%), and lack of analgesia at home (71/561, 12.7%). Analgesia was offered to 328/560 (58.6%) children in the ED and 283/328 (72.6%) caregivers accepted. The most common reason for not accepting analgesia was child refusal (20/45, 44.4%).Conclusion: Most caregivers do not offer analgesia to their child prior to arriving in the ED despite high levels of pain and an awareness of it. Despite high rates of acceptance of analgesia in the ED, misconceptions are common. Knowledge translation strategies should dispel caregiver misconceptions, and highlight the impact of pain on children and the importance of analgesia at home.